PENGEMBANGAN MEDIA PEMBELAJARAN FLIP BOOK BERBASIS EKOPEDAGOGIK APPROACH PADA PEMBELAJARAN IPS KELAS AWAL SEKOLAH DASAR: PENGEMBANGAN MEDIA PEMBELAJARAN FLIP BOOK BERBASIS EKOPEDAGOGIK APPROACH PADA PEMBELAJARAN IPS KELAS AWAL SEKOLAH DASAR - Nasution, Yusra; Husna Parluhutan Tambunan; Sri Mustika Aulia; Masta Marselina Sembiring; Dody Feliks Pandimun Ambarita; Dila Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Research objectives for developing flip book learning media based on an eco-pedagogical approach in early elementary school social studies learning. The research method is research (Research & Development). This development and research used the ADDIE model with research procedures, namely analysis, design, development, implementation and evaluation. The research subject is UPT SDN 104201 Kolam. The instruments in this research will be used to measure validity and practicality using questionnaires and effectiveness using tests. Data collection techniques for feasibility testing involve material and media experts, practicality involves educational practitioners, and effectiveness testing uses pretest and posttest. Data analysis techniques combine descriptive quantitative and qualitative. The results of the research are that material experts gave a score of 96.3% in the